Chromatographic Removal of Endotoxins: A Bioprocess Engineer's Perspective. (5th July 2012) - Ongkudon, Clarence M.; Chew, Jia Han; Liu, Boyin; Danquah, Michael K.
Abstract : Gram-negative bacteria are widely used for the production of gene-based products such as DNA vaccines and bio-drugs, where endotoxin contamination can occur at any point within the process and its removal is of great concern. In this article, we review the structures of endotoxin and the effects that it causes in vivo . The endotoxin removal strategies are also discussed in the light of the different interaction mechanisms involved between endotoxins and bioproducts particularly plasmid DNA and proteins. For most cases, endotoxin removal is favoured at a highly ionic or acidic condition. Various removal methods particularly chromatography-based techniques are covered in this article according to the relevant applications.